Influence of the degree of infiltration of modified activated carbons with CuO/ZnO on the separation of NO at ambient temperatures - Uta Sager; Eckhard Däuber; Dieter Bathen; Christof Asbach; Frank Schmidt; Jo-Chi Tseng; Andre Pommerin; Claudia Weidenthaler; Wolfgang Schmidt (Adsorption Science & Technology)
The reduction of NO 2 in air at ambient temperatures with activated carbons can be increased by the infiltration of metal oxide nanoparticles into the sorbents. The NO 2 is first adsorbed to the activated carbon and subsequently catalytically reduced to physiologically neutral substances by the metal oxides. The catalytic reduction at ambient temperatures is rather slow. In a former study concerning the application in cabin air filters, it was shown that the modification of activated carbon with 5 wt% CuO/ZnO leads to reduced breakthrough of NO 2 and that the adsorbent was able to regenerate between repeated NO 2 adsorption cycles. Here we show that the efficiency of the sorbent can be more than doubled by increasing the metal oxide infiltration to 20 wt% whereas a further increase in loading yields no additional improvement, due to a partial transformation of the oxidic compounds.